Studying predator foraging mode and hunting success at the individual level with an online videogame. (4th July 2022) - Fraser Franco, Maxime; Santostefano, Francesca; Kelly, Clint D; Montiglio, Pierre-Olivier
Abstract: Predator–prey interactions are important drivers of community and ecosystem dynamics. With an online multiplayer videogame, we propose a novel system to explore within population variation in predator hunting mode, and how predator–prey behavioral interactions affect predator hunting success. We empirically examined how four predator foraging behaviors covary at three hierarchical levels (among environments, among individuals, and within individuals) to assess the structure of predator hunting mode. We also investigated how prey activity affects the foraging behavior and hunting success of predators. Our study supports key findings on predator foraging mode and predator-prey interactions from behavioral ecology. We found that individual predators displayed a diversity of hunting tactics that were conditioned by prey behavior. With prey movement, individual predators specialized either as cursorial or ambush hunters along a continuum of their hunting traits, but also shifted their strategy between encounters. Both types of hunters were generally better against slower moving prey, and they achieved similar prey captures over the sampling period. This suggests that virtual worlds supporting multiplayer online videogames can serve as legitimate systems to advance our knowledge on predator–prey interactions. Abstract : Identifying the behavioral mechanisms underlying predator success is critical to accurately predicting how predators impact prey populations. Because behaviors are often difficult to study in natural systems, we used an online videogame that simulates predator–prey interactions. Our study demonstrates that while predators display a variety of hunting strategies driven by prey behavior, each strategy was equally successful.